Orthokeratology lenses with increased compression factor (OKIC): A 2-year longitudinal clinical trial for myopia control. Issue 1 (February 2023) - Lau, Jason K.; Wan, Kin; Cho, Pauline
Abstract: Purpose: To investigate the effectiveness of orthokeratology ( ortho -k) lenses and corneal changes with increased compression factor for myopia control over a 2-year period. Methods: Young participants (age: 6–<12 years), with low myopia (0.50–4.00 D) and low astigmatism (≤1.25 D), were recruited and allowed to choose to wear either single-vision spectacles or ortho -k lenses (randomly assigned to compression factor of either 0.75 or 1.75 D). Axial length and cycloplegic refraction were measured at six monthly intervals for two years by a masked examiner. The myopia control effectiveness was determined by axial elongation. Results: A significant number of control (63 %) dropped out, mainly due to concern about myopia progression (58 %). A total of 75 participants (mean age: 9.3 ± 1.0 years; control: n = 11, ortho -k [0.75 D]: n = 29, ortho -k [1.75 D]: n = 35) completed the study. Considering ortho -k groups only, the mean axial elongation of participants wearing ortho -k lenses of conventional compression factor (0.75 D) and increased compression factor (1.75 D) were 0.53 ± 0.29 and 0.35 ± 0.29 mm, respectively, over the 2-year study period. The between-group differences in corneal health were not significant at all visits. Conclusion: Participants wearing ortho -k lenses of increased compression factor further slowed axial elongation by 34%, when compared with the conventional compression factor without compromising corneal health. Further investigations are warranted to confirm the potential mechanism of an increased compression factor for improved myopia control effectiveness.